Chordoma of the lumbar spine—A potential diagnosis not to be forgotten! - Rafik Elafram, MD; Oussama Abcha, MD; Majdi Ben Romdhane; Majdi Sghaier, MD; Hedi Annabi, MD (Radiology Case Reports, 2023)
Chordoma is a rare, malignant neoplasm thought to develop from the notochord. It most commonly occurs in the base of the cranium or the sacro-coccygeal region but around 15%-20% affect the vertebral body. Extra-lesional resection with or without adjuvant radiotherapy is generally accepted as the mainstay of treatment for this slow-growing tumor. We present a case whereby a patient with an extensive vertebral body lesion causing caudal compression, treated with spinal decompression and posterior stabilization. This case highlights the importance of pre-operative tissue diagnosis, and that, although rare (0.8 per 100,000), chordoma should always be considered.